Metal Carbide‐Based Cocatalysts for Photocatalytic Solar‐to‐Fuel Conversion. Issue 12 (7th October 2022) - He, Kelin; Campbell, Eric; Huang, Zimo; Shen, Rongchen; Li, Qin; Zhang, Shanqing; Zhong, Yu Lin; Zhang, Peng; Li, Xin
Abstract : Semiconductor‐based photocatalytic solar‐to‐fuel conversion has proven an appealing strategy for achieving carbon‐neutral and green‐hydrogen production. However, almost all semiconductors exhibit unsatisfactory photocatalytic performance due to insufficient surface‐active sites, weak selectivity, and fast charge‐carrier recombination. For these reasons, cocatalyst loading has become an encouraging strategy for improving photocatalytic activity and selectivity. Owing to the scarcity, and cost of noble metal‐based cocatalysts, utilization of low‐cost noble‐metal‐free cocatalysts, such as metal carbide‐based cocatalysts, has aroused tremendous attention. This review highlights some recent crucial advances in active metal carbide‐based cocatalysts for photocatalytic solar‐to‐fuel conversion. First, the fundamentals of metal carbide‐based cocatalysts are presented, including the photocatalytic mechanism, advantages, drawbacks, and design rules. Second, three synthesis approaches of high‐active metal carbide‐based cocatalysts, namely constructing metal carbide nanostructures, epitaxial synthesis of metal carbides on nanostructured carbon, and crystal imperfection construction on metal carbides, are thoroughly addressed. Subsequently, applications of metal carbide‐based cocatalysts in photocatalytic hydrogen production, CO2 reduction, and nitrogen reduction are further discussed. Finally, the crucial challenges and important directions of metal carbide‐based cocatalysts for photocatalytic solar‐to‐fuel conversion are proposed. This review demonstrates some new options for rationally designing and developing novel and efficient metal carbide‐based cocatalysts for highly active and selective photocatalytic solar‐to‐fuel conversion. Abstract : This review highlights some recent crucial advances in the active metal carbide‐based cocatalysts for photocatalytic solar‐to‐fuel conversion, especially focusing on the photocatalytic mechanism, advantages and drawbacks, and design rules of high‐active metal carbide‐based cocatalysts and their various applications in photocatalytic hydrogen production, CO2 reduction, and nitrogen reduction.